(untitled) (Asian Journal of Social Science Studies, 2023)
The eagle is a bird widespread in all cultures and beliefs. Throughout history, it has gained a rich symbolic reference. It appears in antiquity as a royal bird and mythological personification of the gods. The Christian world saw in the eagle a symbol of rebirth, as well as Christ himself. The bird was used in Christian art and culture, also in the Greek liturgy as a soteriological, baptismal and eucharistic symbol. Christian writers and theologians pay much attention to it, deriving its symbolism both from the Bible, and medieval bestiaries as well. It appears in the art of painting and sculpture of many epochs, constituting an important ritual, religious and cult element. Up till now, it is an important element of culture - the eagle is the emblem of many modern countries, which often derive their genesis and origin from legends in which this bird appears.